Enhanced Internal Coating Structure and Light Reflectance of Coated Papers: A Sludge Valorization Process - Altay, Bilge Nazli; Huq, Anamika; Aksoy, Burak; Hailstone, Richard; Demir, Muslum; Aydemir, Cem; Williams, Scott (Amer Chemical Soc, 2023)
Paper mill sludge (PMS) is a high-volume waste of the pulppapermaking industry, containing cellulose fibers. This paper introduces cellulose nanofibers extracted from PMS (CNFsPMS) and their application in paper coatings using a wire-wound coating method to enhance internal and optical properties of paper. Three factors were investigated: (i) CNFsPMS amount, (ii) number of layers, and (iii) surface treatment via a 4 x 2 x 2 factorial design. The experimental responses were tracked by fundamentally important internal properties including porosity, air permeability, thickness, roughness, and optical properties of brightness, gloss, and CIE L*a*b* color coordination. The results showed that CNFPMS enhances porosity to 91 mL/ min, permeability to 0.5 x 10-3 mu m2, and gloss to 29.5 at 1 wt % CNFsPMS applied in two layers with 500 pli calendering. Roughness improves to 2 mu m at all levels of CNFsPMS applied to two layers with 500 calendering. CNFsPMS prevents a decrease in brightness and improves lightness, suggesting more colors can be produced in printing applications. The utilization of PMS for papermaking applications can add value to these underutilized residues and open a new revenue stream by reusing it as a high-value material.
Keywords: paper mill sludge; cellulose nanofiber; coating; structural properties; optical properties; surface treatment; calendering; printing